An analysis of Malaysian retracted papers: Misconduct or mistakes? - Yanti Idaya Aspura, M.K.; Noorhidawati, Abdullah; Abrizah, Abdullah (Springer Verlag, 2018)
Retracted publications are a crucial, yet overlooked, issue in the scientific community. The purpose of this study was to analyze the prevalence, characteristics and reasons of Malaysian retracted papers. The Web of Science and Scopus databases were queried to identify Malaysian retracted publications. Available versions of original articles and publication notices were accessed from journal websites. The publications were assessed for various characteristics, including reason for retraction, based on the Committee on Publication Ethics guidelines, and the authority calling for the retractions. From 2009 to June 2017, 125 Malaysian publications comprising (33 journal articles and 92 conference papers) were retracted. There was a spike in the prevalence of retracted articles in 2010 and 2012 with 42 articles (33.6%) and 41 articles (32.8%) respectively from the 125 retracted articles. The mean time from electronic publication to retraction was 1 year. There is no significant relationship between a journal quartile and the mean number of months to retraction (P = 0.842). The reason for retraction for conference papers was specified as “violation of publication principle”. Journal articles were retracted mainly for duplicate publication, plagiarism, compromised peer review process, and self-plagiarism. Most retracted articles do not contain flawed data; and only 2 retracted articles have been accused of scientific mistakes. The study concludes that retractions were mostly due to the authors misconduct. Despite the increases, the proportion of published scholarly literature affected by retraction remains very small, indicating that retraction represents an uncommon, yet potentially increasing and incipient, issue within Malaysian papers, which publishers as well as editors may have consistently and sufficiently addressed.